Desain Panduan Project based learning berbasis Literasi Kimia dengan Tema Bio-baterai untuk Siswa Kelas XII SMA - Aruna Irani; Eka Yusmaita (Entalpi Pendidikan Kimia, 2022)
This study aims to produce a project-based learning guide design based on chemical literacy with the theme "bio-battery" that can be used to improve student literacy and help students understand chemical concepts, especially voltaic cell material. This guide is designed in accordance with the anatomy of the project based learning model according to Michael Grant (2002) which includes aspects of chemical literacy according to Yael Schwartz (2006)..The content and construct validity tests were carried out by five validators (expert judgments) and will be analyzed using the Aiken's V formula. The results of data analysis in this study showed the Aikens' V value for content validity was 0,91 and construct validity was 0,92. Thus, it can be concluded that the technical guide for Project based learning based on chemical literacy is valid in terms of content and context.